ANALYSIS OF THE IMPLEMENTATION OF HYBRID CONTRACT IN MURABAHAH BIL WAKALAH FINANCING FROM AN INTERNAL PERSPECTIVE BASED ON THE DSN-MUI FATWA AT BSI KC PEMATANG SIANTAR - Marizqa Mustika Dara; Tuti Anggraini; Nuri Aslami (Pena Cendekia Insani, 2025)
This study investigates the internal implementation of the hybrid contract in Murabahah bil Wakalah financing at Bank Syariah Indonesia (BSI), Pematangsiantar Perintis Branch, and evaluates its alignment with the DSN-MUI fatwa. Employing a descriptive qualitative method, data were obtained through in-depth interviews. The research reveals that the execution of the Murabahah bil Wakalah contract at BSI Pematangsiantar Perintis is not entirely in accordance with DSN-MUI Fatwa No. 04/DSN-MUI/IV/2000, as both the Murabahah and Wakalah agreements are conducted concurrently. Ideally, the Murabahah agreement should be concluded only after the bank legally possesses the goods via the Wakalah contract. While the simultaneous implementation simplifies the financing process, there is still a need for enhanced internal comprehension and continuous training to ensure full compliance with Islamic legal principles.